Power Harvesting Using Piezoelectric Shoe For External Power Storage - Mohammad Saffri Mazalan; Roslina Mohamad; Murizah Kassim; Shahrani Shahbudin (Institute of Advanced Engineering and Science, 2018)
The demands for portable energy source have increased because most portable electronic device needs the extra energy throughout the day due to the user’s increase in power consumption. Hence, a piezoelectric power harvesting shoe circuit with storage mechanism capabilities is designed by using piezoelectric disc material, 1N4007 bridge rectifiers, USB cables, and an external power storage. Piezoelectric disc material of 27mm and 35 mm in size that produces AC voltage when applied pressure is embedded in shoe’ insole and the output AC voltage is converted using a bridge rectifier for each material. The output is connected to a USB cable and can be connected to the external power storage during power harvesting. Different sizes of piezoelectric disc produce different amount of voltage and are also affected by the pressure applied to it. An amount of 5V is the requirements needed to charge an external device. The 27mm disc produces a voltage of 3V to 5V depending on the pressure applied while the 35mm disc produces 4V to 6.2V. Piezoelectric disc material is an alternative way to harvest energy when embedded to a shoe with an added storage capability as it solves the problem of needing the extra energy for electronic devices.